ANALYSIS OF LOCAL GOVERNMENT FINANCIAL PERFORMANCE IN THE MANAGEMENT OF THE 2024 PADANGSIDIMPUAN CITY BUDGET - Salma Nailatu Sifa Siregar; Tasya Afriani; Shira Almira Rahman; Iskandar Muda; Andy Mulia (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study analyzes the financial performance of the Padangsidimpuan City Government in managing the 2024 Regional Revenue and Expenditure Budget (APBD). The method used is a descriptive quantitative approach through financial ratio analysis, including fiscal autonomy, local revenue (PAD) effectiveness, efficiency, and expenditure alignment. Data were sourced from the 2024 APBD realization report. The results indicate that financial performance still faces challenges, particularly low fiscal independence due to high reliance on transfer funds from the central government. Efforts to optimize PAD have been made, but they have not fully supported independent development financing. Moreover, the expenditure structure is still dominated by operational spending rather than development spending, which may hinder regional economic growth. Therefore, improvements in revenue optimization, efficiency, and budget allocation are needed to ensure more effective and sustainable local financial management.